Lanchester market structures: A. Japanese approach to the analysis of business competition - Campbell, Nigel; Roberts, Keith (Strategic Management Journal, 1986)
Japanese consultants have used Lanchester's military models to define monopoly, premium, duopoly, oligopoly and polyopoly market structures in which competitive conditions differ. These situations are investigated using the PIMS database. The findings refute the idea that monopoly and premium structures are more stable than the others. Instead movements between structures seem to follow a Markov process.